(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
Culture as knowledge collective, has stored in minds every human. Function language as practices culture among otheralso forexplains meaning sayings . Languagecan be said alsoas wrong one wealth spiritual that owns by a group of humans and together saidspeech commmunity. On ‘s research focused on studyconducted atVillage Kesamben ,Ngadum as wrong one focus study . On data interviews thatobtained ,community village Kesamben is still is very is thick will tradition which has, tradition which still maintained until now is calculation Petung Weton as wrong one thingwhich is obliged to be taken into account to bride woman and man when will starts a lives new. In research this uses study anthropolinguistics withfocuses on form and meaning